Sustainability Of Islamic Microfinance Institutions In Realizing A Green Economy - Widya Sari; Sulistyowati Sulistyowati (Fenomena, 2023)
The essence of the green economy concept is to be the driving force for sustainable development. The green economic vision complements sustainable development, which aims to meet existing demands without endangering future generations. This study aims to determine how effective Islamic Microfinance Institutions at KSSU Harum Dhaha Kediri are in implementing the green economy. The research methodology includes case study-based qualitative research. Obtaining data with a focused open-ended interview type. Data analysis with data reduction, data display, and conclusion. The findings of the study show that Sustainable Islamic Microfinance Institutions in realizing a green economy at KSSU Harum Dhaha Kediri have not entirely run optimally because there is still an increase in NPF realization, namely in 2021 the NPF realization is 4.66%, and in 2022 it is 4.88%. This increase is almost close to the NPF tolerance limit of 5%. So, if the NPF level is declared high, non-performing financing increases. The impact of this increase disrupts the operational or sustainable cycle of institutions in realizing a degree of prosperity that is in line with the green economy concept, which is essentially a driving force for sustainable development. The financing product at KSSU Harum Dhaha Kediri, which shows a trend of increasing sustainability, is the Ijarah Multijasa financing product.